Moderate physical training increases brain insulin concentrations in experimental diabetic rats - Curiacos de Almeida Leme, Jose Alexandre [UNESP]; Gomes, Ricardo Jos [UNESP]; Rostom de Mello, Maria Alice [UNESP]; Luciano, Eliete [UNESP] (Natl Inst Science Communication-niscair, 2008)
Insulin is an important modulator of growth and metabolic function in the central nervous system. The aim of this study was to investigate the influence of swimming physical training (at 32 degrees +/- 1 degrees C, 1 hr/day, 5 days/week, with an overload equivalent to 5% of the body weight, for 4 weeks) oil brain insulin concentrations in alloxan induced type I diabetic rats. Training attenuated hyperglycemia but had no effect on insulinemia in diabetic rats. Hematocrit and blood albumin values remained without changes. Brain insulin did not change in diabetic rats. However, physical training increased the concentration in both control and diabetic rats. It is concluded that in the present experimental conditions, diabetes had no influence oil brain insulin, however moderate physical training increased the hormone in both control and diabetic animals.
Keywords: brain; diabetes; insulin; physical training; rat